ANALISIS PENGARUH TINGKAT KURS DAN SUKU BUNGA BANK INDONESIA DENGAN JUMLAH UANG BEREDAR, TERHADAP TINGKAT INFLASI DI INDONESIA - DWI PUSPITA AGUSTIN (Develop: Jurnal Ekonomi Pembangunan, 2021)
This study discusses the "Analysis of Effect of Bi Interest rates, Money Supply and Exchange Rate Against Inflation Rate In Indonesia Period 2012- 2020 ", aims to determine the effect of BI Rate, Money Supply, and the Exchange Rate on Inflation in Indonesia and using the error correction model Engle-Granger (ECM-EG). The results of this study indicate that the BI Rate has a positive and significant effect on the inflation rate in Indonesia. Meanwhile, money supply and exchange rate Rp/Us dollar have a positive and not significant effect on the rate of inflation in Indonesia.